Drug metabolism and antibiotic resistance in micro‐organisms. (13th June 2017) - Sim, Edith; Ryan, Ali
Abstract : Linked Articles: This article is part of a themed section on Drug Metabolism and Antibiotic Resistance in Micro‐organisms. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.14/issuetoc